Improvement on Wear Resistance of 316 Austenitic Stainless Steel by High Temperature Nitriding Technique - Mohd Khairul Munir B Kamaruzaman, Mohd Khairul Munir (Universiti Teknologi Petronas, 2010)
The purpose of this project is to study on wear resistance of 316L Austenitic Stainless steel and makes an improvement on it by applying high temperature nitriding technique. Wear resistance of current stainless steel in market indeed is not sufficient to sustain this kind of heavy loads. Thus, wear resistance of stainless steel needs to be improved in order to overcome this problem. The process of high-temperature nitriding is investigated as a method of intensifying diffusion saturation with nitrogen for some high-alloy steels of the Ferritic and austenitic types.